The Effectiveness of E-Learning on Learning Activities and Achievements Arabic Students | Faa’iliyyah At Ta’lim Al Iliktruniy Fii Muwajahah Ansyithoh Wa Injjaazaat Ath Thulaab Lita’lim Al Lughoh Al ‘Arobiyyah: فاعلية التعلم الإلكتروني في مواجهة أنشطة وإنجازات الطلاب لتعلم اللغة العربية - Noor Ahmad Azis; Sulthan Syahril; Koderi; Erlina (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The background of this research is that learning Arabic is a lesson that is full of memorization, so it is likely that boredom will arise, and in learning activities and student achievement is still low. The purpose of this study was to determine the effectiveness of implementing e-learning media on students' Arabic learning activities and achievements at MAN 2 Bandar Lampung. The type of research used is quantitative research with an associative approach, namely research that looks for a causal relationship between one x variable and 2 y variables. The population in this study were students of class X. The sample in this study used the Proportionate Stratified Random Sampling technique. The samples in this study were 84 students. Data collection techniques, observation, questionnaires, tests and documentation. The results of the study show that there is an influence of the application of e-learning media on student learning activities and achievements. Research results show the normality and homogeneity prerequisite tests: the significance value of Asiymp. Sig (2-tailed) for e-learning 0.200 is greater than 0.05, the value of learning activities is 0.066 greater than 0.05 and for learning achievement 0.200 is greater than 0, 05. It is concluded that the data is normally distributed. The results of the homogeneity test of the probability value of distributing the questionnaire before using e-learning is sig. 0.308 which means greater than 0.05 while the distribution of questionnaires after the use of e-learning is 0.434 which means greater than 0.05. And the probability value of the questionnaire before using e-learning for learning activities is sig. 0.926 which means greater than 0.05 while the distribution of questionnaires after using e-learning produces a value of 0.678 which means greater than 0.05.